Short‐term prognostic factors for primary sclerosing cholangitis. (31st March 2015) - Watanabe, Takeo; Hirano, Kenji; Tada, Minoru; Isayama, Hiroyuki; Mizuno, Suguru; Arizumi, Toshihiko; Toda, Nobuo; Sugawara, Yasuhiko; Kokudo, Norihiro; Koike, Kazuhiko
Abstract Background It was recently reported that alkaline phosphatase (ALP) levels below 1.5 upper limit of normal (ULN) predicted better prognosis in primary sclerosing cholangitis (PSC). We evaluated whether ALP as well as other laboratory values were useful for the short‐term prognosis of PSC in a Japanese cohort. Methods In 78 patients with PSC (41 males and 37 females, mean onset age 41.9 years), the relationship between nine parameters (albumin, bilirubin, international normalized ratio of prothrombin time [PT‐INR], ALP, aspartate aminotransferase [AST], alanine aminotransferase [ALT], γ‐glutamyl transpeptidase [γ‐GTP], platelet, and calculated Model for End‐Stage Liver Disease [MELD] score), and liver related clinical endpoints (death due to liver failure, variceal bleeding, liver transplantation, and biliary carcinoma) were retrospectively examined. Using receiver operating characteristic (ROC) analysis, we investigated which parameter was useful for predicting the short‐term prognosis. Results Average follow‐up period was 8.6 years. The endpoints were evaluated in 40 patients. Seven patients died of liver failure, three patients developed variceal bleeding, nine patients received liver transplantation from a living donor, 13 patients received certified brain‐dead liver transplantation, and eight patients developed biliary carcinoma. The parameters with an area under the curve (AUC) of more than 0.8 were albumin, bilirubin, PT‐INR, ALP, and MELD score. AUC for ALP was 0.85. The optimal cutoff value was 2.3 ULN. Despite the use or non‐use of ursodeoxycholic acid, short‐term prognosis of patients with an ALP level below 2.3 ULN was good. Conclusions We confirmed that keeping ALP low is associated with better short‐term prognosis in a Japanese cohort. In addition, Alb, Bil, PT‐INR, and MELD score were good predictors.